System of National Accounts 2008. (International Monetary Fund, 2009)
This joint publication of the United Nations, the European Commission, the International Monetary Fund, the Organization for Economic Cooperation and Development, and the World Bank reflects the changes and improvements that have been introduced to the System of National Accounts since its most recent revision in 1993. The System of National Accounts 2008 (2008 SNA) is a statistical framework that provides a comprehensive, consistent and flexible set of macroeconomic accounts for policymaking, analysis and research purposes. The 2008 SNA is expected to receive distinguished attention not only from professionals practicing in the field of national accounts but policy makers, analysts, academia and a broad range of users who rely on macroeconomic information obtainable from the updated system of accounts. It also provides an overarching framework for standards in other domains of economic statistics, facilitating the integration of these statistical systems to achieve consistency with national accounts. The publication that contains the 2008 SNA has been substantially updated from its previous version as a result of a multiyear collaborative project. Annex 3 of the publication provides a detailed description of the new features of the 2008 SNA. The 2008 SNA will support the implementation of international standards in national accounting and provide the methodological basis for improving the international comparability of national accounts data. When adopting the 2008 SNA as the updated new standard of national accounting, the United Nations Statistical Commission encouraged all countries to compile and report their national accounts on the basis of the 2008 SNA as soon as possible. The publication also provides practical new tools to complement the previously published version: a glossary of SNA terms and definitions and a comprehensive index.